The Effectiveness of Mathematics E-Modules with a Contextual Approach on Geometry Matters to Improving Students’ Learning Outcomes - Sukarman Sukarman; Wardani Rahayu; Lukman El Hakim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the development of web-based mathematics teaching materials using Moodle from the Learning Management System (LMS) with a Contextual Approach to Geometry in the eighth grade of junior high school. This research is development research by adapting the Borg and Gall development model, consisting of expert validation, small group trials, and large group trials. It uses the t-test to measure product effectiveness. Data collection techniques used questionnaires and written tests. Data analysis was carried out quantitatively using descriptive and inferential statistics. The effectiveness test results show that the t-table value is 2,988, with a significant level of 0.012 smaller than 0.025 (0.012 <0.025). Based on these results, Ho is rejected, so there is an average difference between the experimental class and the control class. Based on these results, it can be stated that the product developed in the form of an E-mathematical module with a contextual approach effectively improves student learning outcomes in geometry material.